Elastic stiffness coefficients of thenardite and their pressure and temperature dependence - Arbeck, D.; Haussuhl, E.; Vinograd, V.; Winkler, B.; Paulsen, N.; Haussuhl, S.; Milman, V.; Gale, Julian (R Oldenbourg Verlag, 2012)
The elastic stiffness coefficients, cij , of orthorhombic Na2SO4 thenardite (space group Fddd) were measured with an ultrasonic plane wave technique at ambient temperature as a function of hydrostatic pressure in the range of 0.1 – 70 MPa. The variation of the cij in the range of 1 – 5000 MPa was studied with density functional theory (DFT) based calculations. The experimental results and the DFT calculations were used to derive a force-field model, which was then employed to compute lattice parameters and elastic stiffness tensors of thenardite and of two other Na2SO4 polymorphs as functions of the temperature based on quasi-harmonic lattice dynamics. The structural parameters of the three polymorphs measured at high temperatures are reproduced to within 1.7% by the present calculations. Phases II (space group Pbnm) and III (Cmcm) appear to have significantly higher entropies than thenardite in agreement with their metastable formation at higher temperatures.